2015
DOI: 10.5603/piap.a2015.0082
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cough as a Symptom of Laryngopharyngeal Reflux—Two Case Reports

Abstract: Laryngopharyngeal reflux (LPR ) is a complex of symptoms caused by the backflow of gastric contents into the larynx, pharynx, nasopharynx, sinuses and even to the middle ear space.The symptomatology of LPR includes: chronic cough, hoarseness, throat clearing, laryngitis, "globus pharyngeus", swallowing disturbances, postnasal drip, "fetor ex ore". In the article, the authors present two boys with chronic cough, in one of them the asthma was suspected and antiasthmatic treatment was administrated; in our patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…In the context of medical etiologies, one manuscript reported that laryngopharyngeal reflux tends to present in school-age children with globus sensation, in addition to chronic cough, dyspnea, halitosis, and sore throat (Venkatesan et al, 2013). One case report described a 16-year-old boy with a sensation of a lump in his throat who was diagnosed with laryngopharyngeal reflux (Kopka et al, 2016). Gastroesophageal reflux disease (GERD) has been associated with globus pharyngeus presentation in pediatric patients in addition to hoarseness, sinusitis, stridor, and otalgia (Gilger, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of medical etiologies, one manuscript reported that laryngopharyngeal reflux tends to present in school-age children with globus sensation, in addition to chronic cough, dyspnea, halitosis, and sore throat (Venkatesan et al, 2013). One case report described a 16-year-old boy with a sensation of a lump in his throat who was diagnosed with laryngopharyngeal reflux (Kopka et al, 2016). Gastroesophageal reflux disease (GERD) has been associated with globus pharyngeus presentation in pediatric patients in addition to hoarseness, sinusitis, stridor, and otalgia (Gilger, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Блуждающий нерв является общим источником иннервации пищевода и бронхиального дерева. Развитие бронхоспазма происходит опосредовано через блуждающий нерв вследствие раздражения СО пищевода кислым содержимым желудка [29].…”
Section: Introductionunclassified